(untitled) (Revista Brasileira Multidisciplinar, 2024)
In 2022, the Ministry of Health recorded 141,400 scorpion-related accidents in Brazil, including 1,500 severe cases that required hospitalization due to their gravity. The lack of information exposes the population, especially children and the elderly, emphasizing the need for immediate care to prevent complications. In this context, the study aimed to assess the level of knowledge among Pharmacy students at a Higher Education Institution in Rio Grande do Norte, Brazil, regarding scorpionism. Using an online questionnaire, 49 students (predominantly female and aged between 21 and 25 years) were interviewed. Although 93.9% had never been stung by scorpions, 61.7% knew someone who had experienced such an incident. Regarding immediate care, there was a lack of consensus, especially regarding the use of warm or cold compresses. Concerning the use of a tourniquet, 57.1% discouraged it, 10.2% would use it, 8.2% were undecided, and 24.5% could not respond. Regarding the application of substances to the lesion, 63.3% recommended water and soap, 20.4% preferred no application, 8.2% chose 70% alcohol, and 4.1% suggested anti-inflammatory ointments. The results indicate deficient knowledge about scorpionism, possibly due to the absence of specific disciplines, common across various health-related courses. Decision-making about initial care remains uncertain even among university students. Given the potential for complications in the absence of proper treatment, health education is crucial, especially for pharmacists, who play an essential role in community care and can guide the population correctly and effectively.